Characteristics and outcomes of fetal ventricular aneurysm and diverticulum: combining the use of a new technique, fetal HQ - Zhao, Liqing; Wu, Pengfei; Jiao, Xianting; Zhang, Minjie; Jing, Wenhao; Wu, Yurong; Chen, Sun (Frontiers in Pediatrics, 2023)
Objectives Congenital ventricular aneurysms or diverticulum (VA/VD) are rare cardiac anomalies with lack prenatal evaluation data. The present study aimed to provide the prenatal characteristics and outcomes from a tertiary center and the use of new techniques to evaluate the shape and contractility of these fetuses. Methods Ten fetuses were diagnosed with VA or VD, and 30 control fetuses were enrolled. Fetal echocardiography was performed to make the diagnosis. The prenatal echo characteristics and follow-up data were carefully reviewed. The shape and contractility measurements of the four-chamber view (4CV) and both ventricles were measured and computed using fetal fetal heart quantification (HQ). Results A total of 10 fetuses were enrolled, including 4 cases of left ventricular diverticulum, 5 cases of left ventricular aneurysm, and 1 case of right ventricular aneurysm (RVA). Four cases chose to terminate the pregnancy. The RVA was associated with a perimembranous ventricular septal defect. Two cases had fetal arrhythmia, and one case had pericardial effusion. After birth, one case underwent surgical resection at five years old. The 4CV global sphericity index (SI) of free-wall located ventricular outpouching (VO) was significantly lower than the apical ones and the control group (p < 0.01). Four of five apical left VOs had significant higher (>95th centile) SI in base segments, and three of four left VOs in the free-wall had significant lower (< 5th centile) SI in the majority of 24 segments. Compared to the control group, the left ventricle (LV) global longitudinal strain, ejection fraction, and fractional area change were significantly decreased (p < 0.01), while the LV cardiac output of the cases was in the normal range. The transverse fraction shortening of the affected segments of ventricles was significantly lower than the other ventricle segments (p < 0.01). Conclusions Fetal HQ is a promising technique to evaluate the shape and contractility of congenital ventricular aneurysm and diverticulum.